A study on the inverse design of functionally graded curved components with finite element software scripting - Gönczi, Dávid (Design of Machines and Structures, 2025)
Inverse design is an important computational method that determines the optimal material distribution or geometry, particularly in functionally graded materials, to achieve predefined performance targets by tailoring spatially varying properties usually by applying optimisation techniques and other artificial intelligence methods. The purpose of this paper is to study the calculation of basic field variables for curved components (such as curved plates, cylinders) made from functionally graded materials and its implementation into the design process using the scripting environment of a finite element software system. Thermomechanical problems are considered, where the bodies are subjected to combined thermomechanical loading. We examine the characteristics of design optimisation through a simpler, one-dimensional example and explore a few possibilities to facilitate the design process.